2012
DOI: 10.1007/978-3-642-32211-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Resource-Driven CLP-Based Test Case Generation

Abstract: Abstract. Test Data Generation (TDG) aims at automatically obtaining test inputs which can then be used by a software testing tool to validate the functional behaviour of the program. In this paper, we propose resource-aware TDG, whose purpose is to generate test cases (from which the test inputs are obtained) with associated resource consumptions. The framework is parametric w.r.t. the notion of resource (it can measure memory, steps, etc.) and allows using software testing to detect bugs related to non-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The closest studies are the ones from De Oliveira et al [25] and Albert et al [26], which fit the context of this study. However, both studies leveraged only a subset of proxies investigated in this paper, focused on different testing problems and techniques.…”
Section: Performance Proxiessupporting
confidence: 67%
See 2 more Smart Citations
“…The closest studies are the ones from De Oliveira et al [25] and Albert et al [26], which fit the context of this study. However, both studies leveraged only a subset of proxies investigated in this paper, focused on different testing problems and techniques.…”
Section: Performance Proxiessupporting
confidence: 67%
“…De Oliveira et al [25] investigated performance proxies in the context of regression testing. Albert et al [26] proposed three performance proxies for symbolic execution and showed their benefits on example programs. Symbolic execution can be used as an alternative technique to generate test cases rather than GAs; however, it has various limitations widely discussed in the literature [42,43], such as the path explosion problem, it cannot handle external environmental dependencies, and complex objects.…”
Section: Performance Proxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, previous approaches (e.g., [4,17]) to test case generation based on partial evaluation, the closest to our approach, do not claim full coverage w.r.t. any coverage criteria.…”
mentioning
confidence: 85%
“…Finally, other works have focused on automation. However, most of this research has focused on automating the generation of load test suites [1,13]. For example, [16] proposes an approach to automate the generation of test cases based on specified levels of load and combinations of resources.…”
Section: Related Workmentioning
confidence: 99%